Analisis Strategi Pemasaran dalam Meningkatkan Daya Saing Industri Batik Tulis Giriloyo - Suhairi, Suhairi; Harahap, Efni Yulia Santri; Putra, Musdiansyah; Ramadhani, Nabila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Marketing strategy is the way to create a sustainable competitive advantage for companies that produce goods or services. Market competition is the main challenge for entrepreneurs. The Indonesian batik production industry in Wukirsari Village is a real example. This research aims to analyze the competitive marketing strategy of the Giriloyo batik industry globally. The author uses a qualitative descriptive method for this research, using literature review as the data collection technique. Survey results show that the marketing strategy of the global Giriloyo tie-dye industry includes product strategy, pricing strategy, sales promotion strategy, and placement strategy, commonly known as the 4Ps.